Complicações Pulmonares Pós-operatórias: Revisão Sistemática - Ana Mafalda Bica Tavares (2021)
Introduction: Postoperative pulmonary complications (PPCs) are common events associated with increased morbidity and mortality that negatively affect clinical and financial outcomes in healthcare. The aim of this systematic review was to describe the current evidence underpinning our understanding of PPCs and to highlight conditions that require postoperative noninvasive ventilation (PNIV) or re-intubation with postoperative mechanical ventilation (POMV). Methods: Published reports of randomized control trials (RCTs) evaluating postoperative pulmonary complications were searched using the National Library of Medicine's Pubmed database and Cochrane library inclusive to November 29, 2020. Data involving incidence of PPCs, PNIV, POMV and length of hospital stay were extracted from each study. Results: Thirteen studies that involved 6609 patients were enrolled for the analysis. Only four RCTs yielded statistically significant results. Intraoperative ventilation strategies, more specifically protective lung ventilation (PLV) with low tidal volume and positive end-expiratory pressure (PEEP) and pressure-controlled (PCV) ventilation, as well as postoperative ventilation strategy of continuous positive airway pressure (CPAP) with standard oxygen therapy were the only procedures that clearly reduced the incidence of PPCs. PLV with low tidal volume and PEEP also diminished the need for postoperative noninvasive ventilation, as well as intraoperative mechanical ventilation with a vital capacity maneuver followed by 10 cm H2O of PEEP. Postoperative ventilation strategy of CPAP with standard oxygen therapy was the only procedure that reduced the need for reintubation. Conclusions: There are intraoperative and postoperative ventilation strategies available aiming to reduce postoperative noninvasive ventilation (PNIV) or re-intubation with postoperative mechanical ventilation (POMV).